Reappraisal of IgG subclass deficiencies: a retrospective comparative cohort study - Dogru, Damla; Dogru, Yagmur; Atschekzei, Faranaz; Elsayed, Abdulwahab; Dubrowinskaja, Natalia; Ernst, Diana; Witte, Torsten; Gödecke, Vega; Sogkas, Georgios (Frontiers in Immunology, 2025)
ObjectiveThe aim of the present study was to investigate the clinical spectrum of IgG subclass deficiencies (IgGSDs) and assess the relative clinical significance of diagnosing each specific IgGSD disorder as compared to the common variable immunodeficiency (CVID).MethodsThe clinical spectrum and immunological findings from 96 patients, diagnosed with diverse IgGSDs, were retrospectively evaluated. Specific IgGSDs were compared with each other and a cohort of 270 patients with CVID.ResultsIn comparison to CVID, recurrent lower respiratory tract infections (LRTIs) and bronchiectasis were rarer in IgGSDs, while recurrent mucocutaneous herpes simplex virus reactivations were more common. With respect to autoimmunity, IgGSDs were associated with arthritis, while autoimmune cytopenias were less frequently observed than in CVID. Among IgGSDs, herpes zoster was more common in IgG3SD. Arthritis was more prevalent in IgG1 + 3SD. Given its association with LRTI, splenomegaly, immune thrombocytopenic purpura, and the lower class-switched memory B-cell counts, IgG2 + 4SD is the IgGSD that rather resembles CVID.ConclusionsComparative evaluation of phenotypes and treatments of patients with IgGSDs and CVID reveals distinct features, suggesting the differential clinical significance of diagnosing IgGSDs. The differential clinical expressions of IgGSDs highlight the need for studying each IgGSD separately in order to optimize disorder-specific follow-up procedures and prophylactic anti-infective measures.